Pengembangan Media Pembelajaran Audio Visual Berbasis Website Canva Pada Mata Pelajaran IPAS Topik Perkembangbiakan Tumbuhan di Kelas IV Sekolah Dasar - Kamila, Lila; Taufik, M; Dewi, Ratna Sari (Universitas Muhammadiyah Magelang, 2023)
This research aims to develop audio visual learning media based on the Canva website in the science and sciences subject on the topic of plant reproduction in class IV elementary school. This research is development research/R&D (Research and Development) using the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The subjects of this research are teachers and students of class IV at SDN Singarajan, based on the lack of utilization of existing facilities at the school. , one of which is the use of digital-based learning media. The trial results show a very high level of feasibility of the learning media, the resulting learning media has a level of validity from the two material expert validators, obtaining an average percentage of 89.9% of the